Phytochemical screening and biological evaluation of Salvia hydrangea Dc. ex Benth. growing in eastern Anatolia - TAŞKIN, TURGUT (My University, 2022)
Salvia species have lately gained significant interest as a result of their suitable utilization in various industries. In the current study, S. hydrangea, one of the most consumed sages in the eastern region of Turkey, has been evaluated for phytochemical composition as well as in vitro pharmacological potential comparatively for the first time. The phytochemical composition of S.hydrangea was investigated by LC-MS/MS, GC-FID, and GC/MS. To reveal its biological activities, antioxidant, antimicrobial, and also acetylcholinesterase activities of different solvent extracts such as water, n-hexane, chloroform, and methanol were determined. According to GC-GC/MS analysis, the primary components of the oil were identified as camphor (46.0%), 1,8-cineole (7.5%), camphene (6.8%), limonene (6.5%), beta-pinene (6.11%) and alpha-pinene (5.6%). Additionally, in the infusion and methanol extract, rosmarinic acid and luteolin glycoside were detected as predominant phenolics by LCMS/MS. In DPPH center dot, CUPRAC, and FRAP test results of the samples indicated strong to moderate antioxidant ability in all samples studied, additionally, among them, the infusion exhibited significant acetylcholine inhibition properties comparable with galanthamine. With regard to antimicrobial activity, all of the tested microorganisms had MIC values ranging from 15 to 2000 mu g/mL. Based on these findings, S. hydrangea may have promising properties for a variety of industrial applications in the pharmaceutical, food, and cosmetic industries. (C) 2022 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; BİTKİ BİLİMLERİ; Bitki ve Hayvan Bilimleri; Tarım ve Çevre Bilimleri (AGE); PLANT SCIENCES; PLANT & ANIMAL SCIENCE; Agriculture & Environment Sciences (AGE); Küçük hayvanlar; Bitki Bilimi; Sağlık Bilimleri; Yaşam Bilimleri; Small Animals; Plant Science; Health Sciences; Life Sciences; Salvia hydrangea; Volatile oil; Antimicrobial; GC-GC/MS; Antioxidant activity; LC-MS/MS; VITRO ANTIOXIDANT PROPERTIES; ESSENTIAL OILS; PHENOLIC COMPOSITION; OFFICINALIS L.; ROSMARINUS-OFFICINALIS; ACETYLCHOLINESTERASE; CONSTITUENTS; SPP.; FOOD; SAGE